Perylenediimide based N-type polymer for vertical organic electrochemical transistors - Ting Wang; Songlin Mo; Qilin Peng; Shenhao Li; Saizhe Chen; Xuanzheng Li; Hongxiang Li; Yimin Sun; Jianhua Chen (Materials Research Express)
Advanced high-performance n-type organic mixed ionic-electronic conductors (OMIECs) are essential for the realization of low-power complementary circuits and biosensors based on organic electrochemical transistors (OECTs). However, their development is still hindered by material-related limitations, presenting considerable challenges for future progress. In this work, we designed and synthesized a novel n-type polymeric OMIEC, PDI-TT, utilizing perylenediimide (PDI) as electron withdrawing building block. The PDI-TT was subsequently integrated into a vertical organic electrochemical transistor (vOECT), which exhibits a low threshold voltage of 0.035 V, a moderate transconductance of 2.8 mS, a high current on/off ratio (I _ON /I _OFF = 10 ^5 ), and fast response times ( τ _ON / τ _OFF = 4.1 ms/3.3 ms). Furthermore, the device maintains 98.6% of its initial current after more than 1000 ON−OFF switching cycles in an NaCl aqueous solution, demonstrating excellent stability. These characteristics make it a promising candidate for n-type OECT applications. This research provides new insights into PDI-based polymers for OECTs, emphasizing their potential for advanced bioelectronic applications.